"Top-down" fabrication of anisotropic, lightweight, super-amphiphobic, and thermal insulating rattan aerogels. (August 2022) - Han, Xiaoshuai; Wu, Weijie; Tian, Zhiwei; Wang, Jingwen; Zhang, Lei; Han, Jingquan; Li, Shanshan; Jiang, Shaohua
Abstract: Lightweight and sustainable aerogels have been a growing interest for thermal insulation applications due to current environmental and energy challenges. The design of cellulose-based aerogels with thermal insulation, hydrophobic, and oleophobic performance is the future development direction for building energy-efficient buildings. Herein, an anisotropic, lightweight, super-amphiphobic and thermal insulating rattan aerogel was fabricated by a three-step process of delignification, freeze-drying, and silylation. The prepared rattan aerogel exhibits anisotropic thermal properties with a low thermal conductivity of 0.030 W m –1 K –1 in the radial direction and 0.056 W m –1 K –1 in the axial direction due to the run-through channel skeleton and the structure of the insulating cages. Moreover, the silylated rattan aerogel shows super-amphiphobic performance (water contact angle ∼164° in the cross section and ∼156° in the radial section; oil contact angle ∼158° in the cross section and ∼154° in the radial section). The excellent anisotropic thermal performance, abundance, sustainability, and superb amphiphobicity of the rattan aerogel make it highly promising for green buildings and thermal management applications. Graphical abstract: An anisotropic, lightweight, super-amphiphobic and thermal insulating rattan aerogel was fabricated by a three-step process of delignification, freeze-drying, and silylation. Image 1 Highlights: A "top-down" method was introduced to fabricate rattan aerogels (RAs). The rattan aerogel exhibited superb thermal insulating and amphiphobic properties. Low thermal conductivity was ascribed to hierarchical structure and insulating cages. Silylation endowed RAs superior hydrophobic and oleophobic performance.